1972
DOI: 10.1287/mnsc.19.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Solution of a Satisficing Model for Random Payoff Games

Abstract: In this paper, we consider a "satisficing" criterion to solve two-person zero-sum games with random payoffs. In particular, a player wants to maximize the payoff level he can achieve with a specified confidence. The problem reduces to solving a nonconvex mathematical programming problem. The main result shows that solving this problem is equivalent to finding the root of an equation whose values are determined by solving a linear problem. This linear problem results from maximizing the confidence with fixed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…In [2] we have shown that if all a tj have a finite range then p lf p 2 can be chosen so that w(t) = -for all t in [p 1? p 2 ] and (1.2) becomes the expected…”
Section: ) St £ X ƒ P(ay > T)w(t) Dt> a V/ Jc > 0 Vimentioning
confidence: 99%
See 4 more Smart Citations
“…In [2] we have shown that if all a tj have a finite range then p lf p 2 can be chosen so that w(t) = -for all t in [p 1? p 2 ] and (1.2) becomes the expected…”
Section: ) St £ X ƒ P(ay > T)w(t) Dt> a V/ Jc > 0 Vimentioning
confidence: 99%
“…Case (d) can be solved in several different ways depending on the goals of the players. This has been the subject of study in [2] and [3], Case (b) was introduced by Fourgeaud et al in [5]. There the case of a one person random payoff game against nature is analyzed and a method of solution for such a game is given.…”
Section: D) the Players Have Complete Information About The Distributmentioning
confidence: 99%
See 3 more Smart Citations